2010
DOI: 10.3345/kjp.2010.53.6.694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of severe neonatal morbidities on long term outcome in extremely low birthweight infants

Abstract: PurposeTo assess the validity of individual and combined prognostic effects of severe bronchopulmonary dysplasia (BPD), brain injury, retinopathy of prematurity (ROP), and parenteral nutrition associated cholestasis (PNAC).MethodsWe retrospectively analyzed the medical records of 80 extremely low birthweight (ELBW) infants admitted to the neonatal intensive care unit (NICU) of the Severance Children's Hospital, and who survived to a postmenstrual age of 36 weeks. We analyzed the relationship between 4 neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
2
15
0
1
Order By: Relevance
“…Infants and young children with BPD are at increased risk of rehospitalization and numerous complications during home management (Table 4) [1,30]. The risk of poor outcomes, including death, in VLBW/ELBW infants is greatest for those with severe BPD, brain injury, and severe ROP [39]. The incidence of medically related problems is usually greatest during the first 2 years after discharge but can persist beyond very early childhood [40].…”
Section: Related Medical Problemsmentioning
confidence: 99%
“…Infants and young children with BPD are at increased risk of rehospitalization and numerous complications during home management (Table 4) [1,30]. The risk of poor outcomes, including death, in VLBW/ELBW infants is greatest for those with severe BPD, brain injury, and severe ROP [39]. The incidence of medically related problems is usually greatest during the first 2 years after discharge but can persist beyond very early childhood [40].…”
Section: Related Medical Problemsmentioning
confidence: 99%
“… concluded that the diagnosis of any one, two or three morbidities in the neonatal period were able to predict late death or disability at the age of five. This model was applied using a small Korean cohort of extremely premature infants and produced similar results. Our results only demonstrated that having two morbidities could predict death or disability at the age of seven.…”
Section: Discussionmentioning
confidence: 83%
“…BPD patients show higher mortality risk, 18 obstructive respiratory symptoms and frequent airway infections (especially caused by respiratory syncytial virus), often until the age of 8. 19 They also have lower cognitive abilities and performances at school; 20 they suffer from reduced motor skills gastroesophageal reflux disease, 21 hearing loss and ROP.…”
Section: Nutrition At Dischargementioning
confidence: 99%